2x+8-13=3x+4

Simple and best practice solution for 2x+8-13=3x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+8-13=3x+4 equation:



2x+8-13=3x+4
We move all terms to the left:
2x+8-13-(3x+4)=0
We add all the numbers together, and all the variables
2x-(3x+4)-5=0
We get rid of parentheses
2x-3x-4-5=0
We add all the numbers together, and all the variables
-1x-9=0
We move all terms containing x to the left, all other terms to the right
-x=9
x=9/-1
x=-9

See similar equations:

| x-2=9x+1 | | 2x+3+x-1=x+4 | | 27-6=8.25x | | 3(m-10)+1=2(m-8) | | 5(a+a+a=) | | X.2(4x-3)-8=4+2x | | 8t=7t+7 | | 96+4x+4x+(5x+2)+(5x+8)=540 | | -4.3g=25 | | x-3/x=3/12 | | -3z-1=+2-1 | | 12x+5=15x-25 | | -4+-20d=4 | | 4(x-2)-(1/5)(20x+5)=32 | | 4(5x+2)=20x-7 | | 5(x+9)=27 | | 4=1x+46 | | -5(4n+12)+2n=12(n-5) | | 3.4−0.2x=2.9+1.8x | | 6(x-2)+5=-x | | 4(x–3)+8=92 | | (2x+2)+(2x+2)+(2x+2)+(2x+2)=0 | | 11+3x-7=6x+5=3x | | -6+9p=8p | | 12−6(8u−5)=−54 | | 2-5(x+10)=6+3x | | 4(x+3.29)=11.16 | | -9p=9-8p | | 2(x+2)=110 | | -7i(-8i)=0 | | 10(-2x-3)=6(-2x-9) | | 7(4w+2)/3=-8 |

Equations solver categories